The effect of three major co-morbidities on quality of life and outcome of patients with heart failure with reduced ejection fraction - Benes, Jan; Kotrc, Martin; Jarolim, Petr; Hoskova, Lenka; Hegarova, Marketa; Dorazilova, Zora; Podzimkova, Mariana; Binova, Jana; Lukasova, Marianna; Malek, Ivan; Franekova, Janka; Jabor, Antonin; et al. (ESC heart failure, 2021)
AIMS: Diabetes mellitus, chronic obstructive pulmonary disease, and chronic kidney disease are prevalent in patients with heart failure with reduced ejection fraction (HFrEF). We have analysed the impact of co-morbidities on quality of life (QoL) and outcome. METHODS AND RESULTS: A total of 397 patients (58.8 ± 11.0 years, 73.6% with New York Heart Association functional class ≥3) with stable advanced HFrEF were followed for a median of 1106 (inter-quartile range 379-2606) days, and 68% of patients (270 patients) experienced an adverse outcome (death, urgent heart transplantation, and implantation of mechanical circulatory support). Chronic obstructive pulmonary disease was present in 16.4%, diabetes mellitus in 44.3%, and chronic kidney disease in 34.5% of patients; 33.5% of patients had none, 40.0% had one, 21.9% had two, and 3.8% of patient had three co-morbidities. Patients with more co-morbidities reported similar QoL (assessed by Minnesota Living with Heart Failure Questionnaire, 45.46 ± 22.21/49.07 ± 21.69/47.52 ± 23.54/46.77 ± 23.60 in patients with zero to three co-morbidities, P for trend = 0.51). Multivariable regression analysis revealed that furosemide daily dose, systolic blood pressure, New York Heart Association functional class, and body mass index, but not the number of co-morbidities, were significantly (P < 0.05) associated with QoL. Increasing co-morbidity burden was associated with worse survival (P < 0.0001), lower degree of angiotensin-converting enzyme inhibitor/angiotensin receptor blocker treatment (P = 0.001), and increasing levels of BNP (mean of 685, 912, 1053, and 985 ng/L for patients with zero to three co-morbidities, P for trend = 0.008) and cardiac troponin (sm-cTnI, P for trend = 0.0496), which remained significant (P < 0.05) after the adjustment for left ventricular ejection fraction, left ventricular end-diastolic diameter, right ventricular dysfunction grade, body mass index, and estimated glomerular filtration rate. CONCLUSIONS: In stable advanced HFrEF patients, co-morbidities are not associated with impaired QoL, but negatively affect the prognosis both directly and indirectly through lower level of HF pharmacotherapy and increased myocardial stress and injury.
Keywords: Stroke Volume; Co-morbidities; funkce levé komory srdeční; Myocardial stress; Heart failure; Morbidity; kvalita života; Follow-Up Studies; tepový objem; morbidita; následné studie; Quality of life; Humans; srdeční selhání; Quality of Life; Myocardial injury; Ventricular Function, Left; Heart Failure; lidé; Outcome